Kepuasan Pengunjung Tentang Fasilitas Pelengkap di Daya Tarik Wisata Taman Bunga Puncak Tonang Kabupaten Pasaman - Angela Tri Kurnia Sari; Hijriyantomi Suyuthie (Universitas Negeri Padang, 2022)
This study aims to determine the review of tourist satisfaction so that tourism utilization goes well. The purpose of this study was to describe tourist satisfaction with complementary facilities in the tourist attraction